HISTORIOGRAPHY AND THE NIGERIAN VIDEO FILM IN YORUBA: A STUDY OF MUFU OLOΌOSA OKO (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
The symbiotic relationship between art and history is inevitable. Art and history relate to sustain society. This essay, therefore, focuses on Mufu Oloosa Oko, a Yoruba video film to reveal the extent at which history is brought back to the memory lane as an artistic contribution for the survival of the nation from criminalities. The essay adopts content analysis approach of qualitative research method of both primary and secondary data, using Reader-response theory. The paper finds that the historical criminalities displayed in the film are handled in order to deter other interested perpetrators. The paper discovers also that history can be used to propel progress in the country when it is explored in arts generally, and in film, in particular, as a leading popular culture in Nigeria. It contends that there is no justification for criminalities. It also emphasises the relevance of history and art in fighting criminalities in the society. It concludes that the source of the film (history) and the theme are relevant as they provide avenue for quality assurance in film art in the contemporary Nigerian society. The essay recommends that: 1) government should take histories seriously as they are relevant to the sustenance of the society; 2) criminalities must be tackled efficiently by government to maintain a safe society 3) government should look into the direction of using film as a medium of educating the society in order to eradicate or reduce criminalities in the society; 4) government should provide adequate measures whereby law enforcement agents will not use their positions against the people they are meant to protect; 5) and finally, government should always make sure that any erring enforcer of law is punished according to the laws of the land.